Pengaruh Free Cash Flow, Return On Asset, Debt To Equity Ratio, Dan Economic Value Added Terhadap Return Saham : (Studi Pada Saham Perusahaan LQ45 di BEI Periode 2015-2019) - Hastutie Nur Andriati; Sherina Baguna (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
The research aims to examine and empirically analyze the presence of information content of Free Cash Flow, Return On Assets, Debt to Equity Ratio and economic value added on stock returns in the study of LQ45 companies on the Indonesia Stock Exchange from 2015 to 2019. This study uses a quantitative approach with a population the research is the companies that are included in the LQ45 Index on the Indonesia Stock Exchange in 2015, 2016, 2017 2018, and 2019. Financial report data is obtained through access to www.idx.co.id. The number of samples used in this study were 45 samples. The analytical technique used in this study is multiple regression in order to obtain a comprehensive picture of the relationship between one variable and another. This study uses of 5%. Based on the results of this study Free Cash Flow, Return On Assets, Debt to Equity Ratio and Economic Value added partially and simultaneously have no significant effect on stock returns with a significance value of 0.697, 0.744, 0.216 and 0.242, respectively, no significant effect on stock returns.